IMPACT learning : librarians at the forefront of change in higher education - Maybee, Clarence; ScienceDirect eBooks (Cambridge, MA : Chandos Publishing, an imprint of Elsevier, 2018)
IMPACT Learning: Librarians at the Forefront of Change in Higher Education describes how academic libraries can enable the success of higher education students by creating or partnering with teaching and learning initiatives that support meaningful learning through engagement with information. Since the 1970s, the academic library community has been advocating and developing programming for information literacy. This book discusses existing models, extracting lessons from Purdue University Libraries' partnership with other units to create a campus-wide course development program, Instruction Matters: Purdue Academic Course Transformation (IMPACT), which provides academic libraries with tools and strategies for working with faculty and departments to integrate information literacy into disciplinary courses.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed February 19, 2018).
Elsevier
Keywords: Academic librarians; Librarians -- Education (Higher); LANGUAGE ARTS & DISCIPLINES / Library & Information Science / General; Academic librarians; Electronic books